Innate inflammation drives NK cell activation to impair Treg activity. Issue 108 (March 2020) - Dean, Joseph W.; Peters, Leeana D.; Fuhrman, Christopher A.; Seay, Howard R.; Posgai, Amanda L.; Stimpson, Scott E.; Brusko, Maigan A.; Perry, Daniel J.; Yeh, Wen-I.; Newby, Brittney N.; Haller, Michael J.; Muir, Andrew B.; et al.
Abstract: IL-12 and IL-18 synergize to promote TH 1 responses and have been implicated as accelerators of autoimmune pathogenesis in type 1 diabetes (T1D). We investigated the influence of these cytokines on immune cells involved in human T1D progression: natural killer (NK) cells, regulatory T cells (Tregs), and cytotoxic T lymphocytes (CTL). NK cells from T1D patients exhibited higher surface CD226 versus controls and lower CD25 compared to first-degree relatives and controls. Changes in NK cell phenotype towards terminal differentiation were associated with cytomegalovirus (CMV) seropositivity, while possession of IL18RAP, IFIH1, and IL2RA T1D-risk variants impacted NK cell activation as evaluated by immuno-expression quantitative trait loci (eQTL) analyses. IL-12 and IL-18 stimulated NK cells from healthy donors exhibited enhanced specific killing of myelogenous K562 target cells. Moreover, activated NK cells increased expression of NKG2A, NKG2D, CD226, TIGIT and CD25, which enabled competition for IL-2 upon co-culture with Tregs, resulting in Treg downregulation of FOXP3, production of IFNγ, and loss of suppressive function. We generated islet-autoreactive CTL "avatars", which upon exposure to IL-12 and IL-18, upregulated IFNγ and Granzyme-B leading to increased lymphocytotoxicity of a human β-cell line in vitro . These results support a model for T1D pathogenesis wherein IL-12 and IL-18 synergistically enhance CTL and NK cell cytotoxic activity and disrupt immunoregulation by Tregs. Graphical abstract: Working Model Summarizing the Hypothesized Contributions of Elevated IL-12 and IL-18 Levels Toward Failure in Immunoregulation and T1D Pathogenesis. In immune homeostasis (left), regulatory T cells (Treg) suppress activation and function of CD8+T cells, CD4+T cells and NK cells via various mechanisms including competition for IL-2. In settings of increased genetic risk for T1D, exposure to some environmental trigger(s) compound genetic defects to induce a break in tolerance (right), during which time IL-12 and IL-18 levels are elevated and NK cells upregulate CD25. This allows for direct competition with Tregs for IL-2, resulting in decreased Treg IL-2 signaling, STAT5 phosphorylation (pSTAT5), and FOXP3 expression, ultimately abrogating suppression. We hypothesize that this, together with enhanced production of cytokines and cytolytic proteins by CD4+conventional T cells and CD8+cytotoxic T cells, leads to augmented lysis of β-cells (right). Image 1 Highlights: IL-12 & IL-18 enhance NK cell and antigen specific CD8 T cell killing. Regulatory T cells (Tregs) lose suppressive capacity and produce IFN-γ. Type 1 Diabetes candidate genes permit CD25 upregulation on NK cells. NK cells exhibit altered receptor balance and are able to compete with Tregs for IL-2 in vitro .